SLANG AS GENERATION IDENTITY: A STUDY OF FAMILY COMMUNICATION OF COLLEGE STUDENTS IN BALIKPAPAN - Ningsih, Era Wahyu (Faculty of Letters Universitas Balikpapan, 2026)
Language is the primary means of communication in social interactions, allowing individuals to convey thoughts, feelings, and information to others. In its development, language undergoes various variations influenced by social factors, age, and the social environment of its speakers. One form of language variation that has developed rapidly among young people is slang. This study aims to analyze the use of slang in family communication among students, including students’ level of knowledge about slang, the intensity of its use within the family, and the forms of slang commonly used in daily communication.